2020
DOI: 10.1186/s42483-020-00070-x
|View full text |Cite|
|
Sign up to set email alerts
|

Suitable methods for isolation, culture, storage and identification of wheat blast fungus Magnaporthe oryzae Triticum pathotype

Abstract: Wheat blast disease caused by a South American lineage of Magnaporthe oryzae Triticum (MoT) pathotype has emerged as a serious threat to wheat production in Bangladesh since its first emergence in 2016. Efficient and suitable methods for isolation, storage, inoculum production and molecular characterization of the pathogen can help in achieving the target of sustainable management of the disease in a relatively short period of time. In this study, we aimed to develop suitable methods for isolation, storage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…2C). These results are consistent with earlier studies which showed that the length of conidia ranged from 22.76−28.56 µm and width 7.85−9.21 µm [35]. The isolate was then subcultured to PDA medium and incubated for 7 days to undergone molecular identification (Fig.…”
Section: Isolation Of Fungal Pathogensupporting
confidence: 91%
“…2C). These results are consistent with earlier studies which showed that the length of conidia ranged from 22.76−28.56 µm and width 7.85−9.21 µm [35]. The isolate was then subcultured to PDA medium and incubated for 7 days to undergone molecular identification (Fig.…”
Section: Isolation Of Fungal Pathogensupporting
confidence: 91%
“…A fungal isolate BTJP 4–5 was obtained in pure culture from the field-infected wheat blast samples by picking up a single conidium and then preserving it at 4 °C on dry filter paper, following the method described earlier [ 47 ]. For this study, this virulent isolate BTJP 4–5 of MoT was retrieved from storage in potato dextrose agar (PDA) medium and incubated at 25 °C for conidia production [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The conidial suspension was prepared from 10-day-old culture plates and the spore concentration was adjusted to ca. 5 × 10 4 conidia mL −1 , as described by [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…A sterilized sealed Pasteur pipette was scraped over the sporulation and loaded with conidia, which was streaked across the agar-water dishes supplemented with chloramphenicol and streptomycin at 100 µg/ml each. Plates were incubated at 25±5°C for 24 hours (12/12 h fluorescent light/darkness) (Farman et al 2017;Gupta et al 2020).…”
Section: Culturing Purification and Storagementioning
confidence: 99%
“…Blasted paper pieces were transferred to a new sterilized plastic dish filled with blue silica and left to dry at room temperature (25°C±5) for five days. Dried paper pieces were transferred to a 2 ml-microtube half-filled with new and sterile blue silica-gel (Figure 5G) and stored in a -10°C freezer (Farman 2002;Farman et al 2017;Gupta et al 2020). Isolates were stored in duplicates as a backup of the entire collection.…”
Section: Culturing Purification and Storagementioning
confidence: 99%